Compact thermal noise model for enhancement mode N‐polar GaN MOS‐HEMT including 2DEG density solution with two sub‐bands. Issue 6 (25th April 2018) - Panda, Deepak Kumar; Lenka, Trupti Ranjan
Abstract : A 135 nm gate length‐based low noise enhancement mode N‐polar double deck T‐shaped gate Gallium Nitride (GaN) Metal Oxide Semiconductor (MOS)‐high electron mobility transistor with double insulating layer of high‐ k dielectrics ZrO2 /HfO2 is proposed. The device exhibits maximum transconductance of 0.55 S/mm, maximum drain current density of 1.4 A/mm and minimum noise figure (NFmin ) of 0.72 dB at 20 GHz. A compact model for Two Dimensional Electron Gas (2DEG) density is developed by explicit solution of surface potential and Fermi level by considering first two sub‐bands of triangular quantum well without using any numerical methods. Based on the surface potential drain current, intrinsic charge, gate capacitance, small signal and thermal noise models are developed. To validate the proposed numerical model, the results are calibrated with TCAD device simulation results and available experimental data from literatures.